2020
DOI: 10.1093/aje/kwaa060
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease and All-Cause Mortality in Male Twins With Discordant Cardiorespiratory Fitness: A Nationwide Cohort Study

Abstract: Whether genetic and familial factors influence the association between cardiorespiratory fitness (CRF) and cardiovascular disease (CVD) is unknown. Two cohorts were formed based on 1,212,295, 18-year-old men that conscripted for military service in Sweden 1972-1996. The first comprised 4,260 twin pairs where twins in each pair had different CRF (≥1 Watt). The second comprised 90,331 non-sibling pairs with different CRF and matched on birth year and year of conscription. Incident CVD and all-cause mortality wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Furthermore, although one twin study has found a single estimate of self-reported physical activity to be associated with reduced risk of all-cause and cardiovascular mortality in monozygotic twin pairs with discordant levels of physical activity [84], several other twin studies have shown other results. For instance, studies that have used either repeated estimates of self-reported physical activity or a single measure of objectively measured physical fitness have found no beneficial associations in relation to major NCDs or mortality in twin pairs with discordant levels of physical activity/fitness [85][86][87], further suggesting that genetic pleiotropy may influence the strong associations of physical activity with various diseases and mortality found in observational studies.…”
Section: Does Exercise Prevent Fractures In Older Adults?mentioning
confidence: 99%
“…Furthermore, although one twin study has found a single estimate of self-reported physical activity to be associated with reduced risk of all-cause and cardiovascular mortality in monozygotic twin pairs with discordant levels of physical activity [84], several other twin studies have shown other results. For instance, studies that have used either repeated estimates of self-reported physical activity or a single measure of objectively measured physical fitness have found no beneficial associations in relation to major NCDs or mortality in twin pairs with discordant levels of physical activity/fitness [85][86][87], further suggesting that genetic pleiotropy may influence the strong associations of physical activity with various diseases and mortality found in observational studies.…”
Section: Does Exercise Prevent Fractures In Older Adults?mentioning
confidence: 99%
“… 254 Moreover, genetic factors may confound the observed association between low levels of physical activity and higher disease and mortality risk. 255 , 256 , 257 …”
Section: Benefits Of Exercise In Homeostatic Resiliencementioning
confidence: 99%
“…It is to some extent an integrated measure of several factors with negative effects on cardiovascular health such as obesity, T2D, smoking, and sedentary activity, but there are genetic factors that contribute to individual variations of CRF. These familiar and genetic factors are also of major importance for the association between CRF and disease in young males [ 66 ].…”
Section: Cardiovascular Healthmentioning
confidence: 99%